(untitled) - Anthony, Scott D. (Boston, Mass., 2009)
Experts agree that the turbulence triggered by the economic shock of 2008 constitutes the 'new normal'. Unfortunately, too many managers have become paralyzed by it, capable only of slashing costs indiscriminately. This title explains how to safeguard your company's profitability during even the toughest recessions.
Keywords: Technological innovations,New products,Đổi mới công nghệ,Sản phẩm mới; Management,Quản lí